Microalgal metabolic engineering strategies for the production of fuels and chemicals. (February 2022) - Kang, Nam Kyu; Baek, Kwangryul; Koh, Hyun Gi; Atkinson, Christine Anne; Ort, Donald R.; Jin, Yong-Su
Graphical abstract: Highlights: Microalgae metabolic engineering for lipid and isoprenoid production is reviewed. Comprehensive metabolic maps with metabolic engineering strategies are presented. Challenges and perspectives of microalgae metabolic engineering are discussed. Abstract: Microalgae are promising sustainable resources because of their ability to convert CO2 into biofuels and chemicals directly. However, the industrial production and economic feasibility of microalgal bioproducts are still limited. As such, metabolic engineering approaches have been undertaken to enhance the productivities of microalgal bioproducts. In the last decade, impressive advances in microalgae metabolic engineering have been made by developing genetic engineering tools and multi-omics analysis. This review presents comprehensive microalgal metabolic pathways and metabolic engineering strategies for producing lipids, long chain-polyunsaturated fatty acids, terpenoids, and carotenoids. Additionally, promising metabolic engineering approaches specific to target products are summarized. Finally, this review discusses current challenges and provides future perspectives for the effective production of chemicals and fuels via microalgal metabolic engineering.